Editorial - Ali Kemal Ozdemir (Cumhuriyet University, 2012)
Dear Colleagues,   As a result of globalization, the English language has inevitably had an active part for journals for increasing impact factors. Thus, become a widely distributed journal worldwide, I invite all authors to submit their papers in English to CDJ. I'm happy to announce that Dr. Sauro has accepted the role of associate editor in CDJ. I'm grateful to him for sparing his time for CDJ. Furthermore, I would like to thank Dr. Foschi and Dr. Kantarci for joining our family. Our journal has become a member of CrossRef. Thus, articles have been published with doi numbers in January 2012 issue. Moreover, accepted articles will be published with doi numbers in online first section. I would also like to once again express my personal gratitude to all authors and editorial board members for their valuable contributions.   Hope to meet in the next issue.   Prof. Dr. Ali Kemal Ozdemir Editor-in-Chief Cumhuriyet Dental Journal